TEACHING TECHNOLOGY AND METHODS OF ECONOMIC DISCIPLINES IN THE TRAINING PROCESS MASTERS OF ECONOMIC PROFILE (Pedagogy of Higher and Secondary Education, 2008)
The article reveals the main questions, connected with the methodology of working out educational and operating programs for the magistrates as well as technological aspects of the realization of these documentary supply.